IMPORTANCE OF PAPANICOLAOU STAINING IN GYNECOLOGIC CYTOLOGY - Agbo-inedu maria lhotu-owoicho; Ajit Pal Singh, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
As we all know pap staining also known as the universal smear is one of the most important procedures in cytology as it is used in gynecologic and non-gynecologic cytology smear. It is one of the most widely used stains in cytology, as it has reduced drastically the diagnosis of cervical cancer by 70% in highly developed countries. Pap smear is very important because it reveals the structure of the cell to be examined. examples include, the cytoplasm, nucleus and all cellular granules.